2014
DOI: 10.1002/dvg.22831
|View full text |Cite
|
Sign up to set email alerts
|

On a possible evolutionary link of the stomochord of hemichordates to pharyngeal organs of chordates

Abstract: Summary As a group closely related to chordates, hemichordate acorn worms are in a key phylogenic position for addressing hypotheses of chordate origins. The stomochord of acorn worms is an anterior outgrowth of the pharynx endoderm into the proboscis. In 1886 Bateson proposed homology of this organ to the chordate notochord, crowning this animal group “hemichordates.” Although this proposal has been debated for over a century, the question still remains unresolved. Here we review recent progress related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…These morphological features gave rise to the name, 'HemiChordates' [9,10 ,11 ]. Recent molecular developmental studies, however, have refuted the presumed homology of the stomochord and notochord [35 ]. The notochord is a key source of secreted factors, including Shh and the BMP antagonists Chordin, Noggin, and Follistatin, essential for neural patterning in vertebrates.…”
Section: The Stomochord and The Pygochordmentioning
confidence: 95%
See 2 more Smart Citations
“…These morphological features gave rise to the name, 'HemiChordates' [9,10 ,11 ]. Recent molecular developmental studies, however, have refuted the presumed homology of the stomochord and notochord [35 ]. The notochord is a key source of secreted factors, including Shh and the BMP antagonists Chordin, Noggin, and Follistatin, essential for neural patterning in vertebrates.…”
Section: The Stomochord and The Pygochordmentioning
confidence: 95%
“…Moreover, the Brachyury gene, a key transcription factor for notochord formation in chordates, is not expressed in the developing stomochord [5,35 ,36 ]. On the other hand, vertebrate prechordal endomesoderm genes, otx, dmbx, and hex, are expressed in the stomochord-forming region and in endoderm [35 ]. Another transcription factor, FoxE, which is thyroidspecific in vertebrates, endostyle-specific in ascidians, and specific to the club-shaped gland in amphioxus, is expressed in the stomochord [3,35 ].…”
Section: The Stomochord and The Pygochordmentioning
confidence: 98%
See 1 more Smart Citation
“…'half-chord') to the chordate notochord, crowning this animal group 'hemichordates'. A recent evodevo study has demonstrated that FoxE is commonly expressed in the stomochord and the chordate endostyle, suggesting that the stomochord is evolutionarily related to the endostyle, rather than the notochord [71]. That is, the two digestive-system-associated structures evolved prior to divergence of chordates from non-chordate deuterostomes [17,18], although the system developed more complex functions in chordates.…”
Section: (D) the Aboral-dorsalization Hypothesismentioning
confidence: 99%
“…Chordates comprise three taxa, cephalochordates, urochordates or tunicates, and vertebrates [2]. These are thought to have originated from a common ancestor of the deuterostomes, together with ambulacrarians, a clade containing echinoderms and hemichordates.…”
Section: Introductionmentioning
confidence: 99%